TANGIBILITY, UNIQUENESS, VOLATILITY ON CAPITAL STRUCTURE AND STOCK RETURN IN THE KOMPAS 100 COMPANIES - Astiti, Ni Putu Yeni; Kepramareni, Putu; Gama, Agus Wahyudi Salasa (Universitas Muria Kudus, 2024)
This research aims to examine the factors influencing stock return. The criteria for sample selection in this study are companies in the Kompas 100 index that publish complete financial reports. The sample in this study consisted of 82 companies with a total observation period of 3 years, resulting in a total of 246 observations. The data analysis technique used to test the research model is SEM–PLS. This research is limited to companies listed on the Indonesia Stock Exchange and included in the Kompas 100 index during 2021-2023. Tangibility positively affects profitability, capital structure, and stock return. Uniqueness has a positive effect on profitability and capital structure. Uniqueness does not affect stock return. Volatility positively affects profitability, capital structure, and stock return. Capital structure does not affect profitability but does affect stock return. Profitability has a positive effect on stock return. Further research will use other variables influencing capital structure, stock return, profitability, and mediating or moderating variables.